Proceedings of the 8th International Conference of Asian Association of Indigenous and Cultural Psychology (ICAAIP 2017) 2018
DOI: 10.2991/icaaip-17.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Self Efficacy in Work Engagement Towards the Nurses in Makassar City

Abstract: Abstract-This research aims to find out how far self-efficacy influences work engagement in nurses in Makassar. Participants in the study were 280 nurses working in six hospitals. The sampling technique used in this research is stratified random sampling. The data analysis performed was the univariate and bivariate analysis with Simple Linear Regression test. The results of this study indicate that self-efficacy contributes to 93% of work engagement in nurses in Makassar. In other words, the better self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…In addition, our results indicate that nurses' work engagement total score and subscales have a significant positive relationship with general SE. This result is in line with the results of many studies (Islamiah & Tamar, 2017; Vujcic, 2019) that have revealed a significant positive relationship between general SE and work engagement. Nurses with high levels of SE can manage their work environment effectively and can face difficulties and mobilize new job resources, resulting in sizeable efforts, motivation at work and the tendency to remain in their workplace and in general increasing their engagement in work as their vigour, absorption and dedication increase (de Simone et al, 2018; Orgamb et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, our results indicate that nurses' work engagement total score and subscales have a significant positive relationship with general SE. This result is in line with the results of many studies (Islamiah & Tamar, 2017; Vujcic, 2019) that have revealed a significant positive relationship between general SE and work engagement. Nurses with high levels of SE can manage their work environment effectively and can face difficulties and mobilize new job resources, resulting in sizeable efforts, motivation at work and the tendency to remain in their workplace and in general increasing their engagement in work as their vigour, absorption and dedication increase (de Simone et al, 2018; Orgamb et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our results indicate that nurses' work engagement total score and subscales have a significant positive relationship with general SE. This result is in line with the results of many studies (Islamiah & Tamar, 2017;Vujcic, 2019) that have revealed a significant positive relationship between general SE and work engagement.…”
Section: The Relationship Between Nurses' Work Engagement Pos and Gen...supporting
confidence: 92%
See 1 more Smart Citation
“…If work engagement is present in nurses, nurses will provide good health services and achieve the mission of the hospital. 35 Work engagement is a mediator variable because it can lead to individual persistence and individual intensity at work, thereby increasing performance. 36 Individuals who are involved in their work tend to do more tasks to provide superior performance in achieving organizational goals.…”
Section: Discussionmentioning
confidence: 99%
“…When the work is done well, then work engagement increases with responsibility and they are more involved in their work, and enjoy their work to achieve good performance and realize the achievement of the organization's vision and mission. 35 Employees who are engaged in their work tend to do more in their duties and provide superior performance in achieving organizational goals and tasks. 38 Human resources are the foundation on which the organization stands.…”
Section: Discussionmentioning
confidence: 99%